PENINGKATAN HASIL BELAJAR LOMPAT JANGKIT MELALUI ALAT BANTU PEMBELAJARAN PADA SISWA KELAS XII IPA 2 SMA NEGERI 1 TERAS KABUPATEN BOYOLALI TAHUN AJARAN 2012/2013 - Muhendri, Ihwan Awang (Jurnal Phederal Penjas, 2013)
Ihwan Awang Muhendri. Increasing ENHANCING LEARNING THROUGH Jumptransmissible LEARNING TOOL FOR STUDENTS IN CLASS XII IPA 2 SMA N 1 TerasBoyolali ACADEMIC YEAR 2012/2013. Thesis, Surakarta: Faculty of Teacher Training andEducation, University of Surakarta of March, December. 2012.This study aims to improve the mastery of the jump transmissible through modifiedteaching aids in class XII IPA 2 SMA Negeri 1 Teras Boyolali academic year 2012/2013.This study uses Classroom Action Research (CAR). The subjects were students ofclass XII IPA 2 SMA Negeri 1 Teras Boyolali academic year 2012/2013 amounted to 35people consisting of 23 girl students and 12 boys students. Data collection techniques withobservation and assessment of mastery jump transmissible. Data analysis techniques used inthis research is descriptive quantitative analysis based on a percentage. Procedures studiesusing cycle phases include planning, action, observation and reflection.Based on the analysis of data obtained by the analysis are as follows: there is anincreasing mastery of the basic techniques of jump transmissible, it can be seen from the dataobtained is significantly increased from the first cycle and second cycle. Before you get anyaction data obtained is 34.29% of the students have mastered the basic techniques of jumptransmissible by category diligence or numbered 12 students. In the first cycle of basictechnical mastery jump transmissible increased to 57.15%, or about 20 students, with thedetails of 13 students getting enough value and 7 students get good grades. While on thesecond cycle increased percentage of 82.85%, with the number of students 29 people, withdetails of 8 students get enough value and 21 students get good grades. This is because byusing a modification of a learning tool that is able to attract students to be more enthusiasticand not easily bored, and the learning process more enjoyable.Based on the results of the study concluded that using a modification of a learningtool to improve jumping ability transmissible in class XII IPA 2 SMA Negeri 1 TerasBoyolali.Keywords: techniques of Jump transmissible, Learning Tools, Ability Jump transmissible.